Retrospective on the importance of sustainability in investor thinking before and after the COVID-19 syndemic - Laura Sanz-Martín; Javier Parra-Domínguez; Juan Manuel Corchado (Global Sustainability)
Abstract Non-Technical Summary The COVID-19 syndemic had a strong impact on financial market volatility. This study compares traditional indices, such as the Standard & Poor’s (S&P) 500 and the Euro Stoxx 50, with their sustainable counterparts; the Dow Jones Sustainability World Index (DJSWI); and the EURO STOXX Sustainability Index. The results show that the sustainable indices were more stable and less volatile before and after the crisis, suggesting that investors perceive less risk in sustainable companies. These findings reinforce the importance of considering sustainability in investment decisions, especially in times of uncertainty.